Heavy metals and essential elements in Commerson's dolphins (Cephalorhynchus c. commersonii) from the southwestern South Atlantic Ocean - Cáceres Saez, Iris; Ribeiro Guevara, Sergio; Dellabianca, Natalia Andrea; Prosser Goodall, Rae Natalie; Cappozzo, Humberto Luis (Environmental Monitoring and Assessment)
A survey of the elemental contents of K, Mg, Mn, Na, Cl, Br, Cs, Co, Rb, Fe, Zn, Al, Ti, V, As, Ag, Au and Cd in liver, kidney and muscle was performed in specimens of Commerson's dolphins (Cephalorhynchus c. commersonii) from subantarctic waters. The concentrations were determined by Instrumental Neutron Activation Analysis and the specimens derives from animals incidentally caught in artisanal fishing nets. Liver had the highest concentrations of Fe, 897(79) μg g-1 DW (dry weight) (average; standard deviation in parenthesis), kidney had the highest Cd, 35 (24) μg g-1 DW; Cl, 9,200 (1,700) μg g-1 DW; Na, 6,800 (1,100) μg g-1 DW and Br, 73(12) μg g-1 DW; and muscle the highest Mg 954 (71) μg g-1 DW. Potassium and Cs concentrations in muscle and kidney ranged in 12,510-13,020 and 0.230-0.252 μg g-1 DW, respectively; Zn and Mn concentrations were similar in liver and kidney (117-122.1 and 3.66-16.5 μg g-1 DW, respectively). Silver was high in liver 5.4(5.0) μg g-1 DW and kidney 1.2(2.7) μg g-1 DW. Gold, Rb, Co and As had no differences among tissues. Likewise, as in other odontocete species, the concentrations of essential elements showed little variation between the specimens analyzed, since they are regulated biochemically; however, heavy metals showed high variability. This study constitutes the first large description of the elemental composition in Commerson's dolphins from subantarctic waters of the South Atlantic Ocean. Fil: Cáceres Saez, Iris. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Ribeiro Guevara, Sergio. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Unidad de Actividad de Ingeniería Nuclear. Laboratorio de Análisis por Activación Neutrónica; Argentina Fil: Dellabianca, Natalia Andrea. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Prosser ...